Assessment of Nutritional Knowledge in Mother’s Under 2-year of age Children - Radhamohan Mudgal; Dr. Charan Singh (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
Introduction: Nutrition is most important role in the growth and development of physical, psychological growth of young children (American Academy of Pediatrics 2016). Millions of children are eating more than what they do not need, and millions are eating too little of the requirement. Aim/Objectives: To assess pre and post intervention score of knowledge regarding recommended nutrition among mothers of children under 2 years of age in the experimental and control group. Methodology: Quasi -experimental pre-test and post-test research design was used to collect data from mothers. Total 300 mothers were enrolled into the study by using purposive sampling technique. The structured knowledge questionnaire used to assess the knowledge regarding balanced diet before and after nutrition educational teaching. Result: The data were gathered and analyzed by using descriptive and inferential statistics. In post-test knowledge score the knowledge of mothers was Adequate 138(92%), moderate 12(8%) in experimental group however knowledge of mothers was moderate 59(39.3%) and inadequate 91(60.7%) in control group There is no significance association between the level of scores and other demographic variables Marital status, religion, Type of family, type of family, type of meal intake, occupation, Family income, previous knowledge, and source of knowledge. The calculated chi-square values were less than the table value at the 0.05 level of significance. The study findings revealed that the mothers were having moderately adequate knowledge regarding dietary practices in prevention of malnutrition. Conclusion: As a result of the study, it was concluded that mother’s education helps the child’s development and this is closely related. NET knowledge will help them to improve the knowledge of nutrition.